FUNGSI KELUARGA DALAM PASANGAN MENIKAH USIA DINI (STUDI KASUS KELURAHAN TEBING TINGGI OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU) - Juliani "; Nurhamlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted at Kelurahan Tebing Tinggi Okura Kecamatan Rumbai Pesisir Kota Pekanbaru. The purpose of this study was to determine the characteristics of married couples at an early age Kelurahan Tebing Tinggi Okura. The focus of this study is the implementation of family functions in married couples early age at Kelurahan Tebing Tinggi Okura. The technique of determining samples in a purposive sampling and determining the number of samples as many as 9 couples who married early age. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. From the research conducted, the authors found that the characteristics of married couples at an early age Kelurahan Tebing Tinggi Okura Are as follows: Research subjects average married at the age of 14-16 years, Research conducted found that the subjects of the average study gave birth to their first child at the age of 15-17 years, the research subjects encountered had a child. Only a pair of research subjects who have two children, Age of the first child in married couples early on average is 5-6 years. Implementation of family functions in the family of married couples early age is the function of Education, Husband considers the child's education is the responsibility of the wife and vice versa. Socialization Function, all study subjects admitted to have expected socialization of their child. Function of Protection, the subject pair applied protection in the form of affection and mutual understanding among fellow family members. Affection function, in giving love of married couple early very careful to all consequence that will be faced. Religious Functions, the subject of research still throwing at each other tasks to give the right of children in religious. Economic Functions, Income that is not sufficient according to the wife for life for days often reap the quarrel in married couples early age. Function Recreation, every family member get comfort from both parties both wife and husband. Biologis function, some research subjects limit the number of children due to economic conditions.Keywords: Characteristics, Marriage, Early Age, Family Function